2012
DOI: 10.1523/jneurosci.5135-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Guided Sensory Comparisons in the Prefrontal Cortex: Contribution of Putative Pyramidal Cells and Interneurons

Abstract: Comparing two stimuli that occur at different times demands the coordination of bottom-up and top-down processes. It has been hypothesized that the dorsolateral prefrontal (PFC) cortex, the likely source of top-down cortical influences, plays a key role in such tasks, contributing to both maintenance and sensory comparisons. We examined this hypothesis by recording from the PFC of monkeys comparing directions of two moving stimuli, S1 and S2, separated by a memory delay. We determined the contribution of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 40 publications
18
61
0
Order By: Relevance
“…Because during this task we used both small and large differences between S1 and S2 directions, we were able to show that the magnitude of comparison effects decreased as the two directions became more similar (Fig 2C). This relationship paralleled behaviorally measured accuracy of direction discrimination and we found that comparison effect was no longer present for pairs of directions that the monkeys were unable to discriminate reliably (Hussar & Pasternak, 2012). This relationship between comparison effect and discrimination performance was further confirmed by finding lower incidence of comparison effects in the monkey with less accurate direction discrimination (see figs 7D & E in (Hussar & Pasternak, 2012)).…”
Section: Decision-related Activity In the Dorsolateral Prefrontal Cortexsupporting
confidence: 67%
See 3 more Smart Citations
“…Because during this task we used both small and large differences between S1 and S2 directions, we were able to show that the magnitude of comparison effects decreased as the two directions became more similar (Fig 2C). This relationship paralleled behaviorally measured accuracy of direction discrimination and we found that comparison effect was no longer present for pairs of directions that the monkeys were unable to discriminate reliably (Hussar & Pasternak, 2012). This relationship between comparison effect and discrimination performance was further confirmed by finding lower incidence of comparison effects in the monkey with less accurate direction discrimination (see figs 7D & E in (Hussar & Pasternak, 2012)).…”
Section: Decision-related Activity In the Dorsolateral Prefrontal Cortexsupporting
confidence: 67%
“…This relationship paralleled behaviorally measured accuracy of direction discrimination and we found that comparison effect was no longer present for pairs of directions that the monkeys were unable to discriminate reliably (Hussar & Pasternak, 2012). This relationship between comparison effect and discrimination performance was further confirmed by finding lower incidence of comparison effects in the monkey with less accurate direction discrimination (see figs 7D & E in (Hussar & Pasternak, 2012)). It is noteworthy, that we observed similar effects during an analogous task involving comparisons of stimulus speeds (Hussar & Pasternak, 2013b).…”
Section: Decision-related Activity In the Dorsolateral Prefrontal Cortexsupporting
confidence: 67%
See 2 more Smart Citations
“…Stimulus selectivity and response latency in putative inhibitory and excitatory neurons of the primate inferior temporal cortex. J Neurophysiol 108: 2725-2736, 2012. First published August 29, 2012 doi:10.1152/jn.00618.2012.-The cerebral cortex is composed of many distinct classes of neurons.…”
mentioning
confidence: 99%